The potential of incorporating local travel route information in addressing systems development to improve urban mobility in Kumasi, Ghana. - Yeboah, Assuamah Abigail (KNUST, 2025)
A Thesis Submitted In Partial Fulfillment Of The Requirements For The Degree Of Master Of Philosophy.